Understanding the Practice Evaluation Process - Gene Elizabeth St. Louis (Taylor & Francis Group, 2023)
ABSTRACTIdentifying the steps of the practice evaluation process, you must understand the basic information regarding definitions and terms commonly used with practice sales. The questions most asked by doctors who are considering purchasing a practice.